Alteridades indígenas e interculturalidade no ensino superior brasileiro: contribuições para a análise da implementação da lei 12.711/2012 - Freitas, Ana Elisa de Castro; Harder, Eduardo (Cadernos CERU, 2020)
This article seeks to contribute to the reflections dedicated to the process of examination and debate on the first decade of validity of Federal Law no. 12,711 / 2012, the so-called Quota Law. It focuses on the trajectory of affirmative policies for the entry and permanence of young indigenous people established during the democratization process of Brazilian higher education, their administrative impasses and their potential. It is understood that such policies inaugurate a new field of knowledge production, whose epistemological contours are defined and perfected in the effective possibility of advancing in the political and pedagogical mechanisms that promote interculturality. The challenge of establishing a systemic horizon capable of promoting an articulation between indigenous school education and higher education, expressed in societal deliberations of indigenous peoples, is considered. Finally, in a context of environmental, economic and political crisis, with repercussions on the erosion of social rights, it is feared for the early emptying of the affirmative actions advocated in the Quota Law, compromising not only the follow-up of the formation of Brazilian indigenous youth, but the democratic agenda for the common good.